2019
DOI: 10.3389/fpsyg.2019.01051
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Standardized Test of Fearful Temperament in Primates: A Sensitive Alternative to the Human Intruder Task for Laboratory-Housed Rhesus Macaques (Macaca mulatta)

Abstract: Standardized and sensitive tests to assess differences in temperament among primates housed in captivity are essential for monitoring welfare and improving science outcomes through reduced noise in data. Fearful temperament in primates has traditionally been assessed using the Human Intruder Test (HIT) in which duration of bodily freeze in response to approach by an unknown human is measured. The HIT is susceptible to variation between facilities in execution, interpretation of data and could be stressful for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The pattern of data observed here is also consistent with findings from Bethell et al (2019) in which macaques showed behavioral inhibition (failure to respond at all to some stimuli) but not response slowing, which might cause one to call the procedure into question. However, it is possible that the lack of effect was due not to a failure of the procedure itself, but of the stimuli we selected.…”
Section: Experiments Onesupporting
confidence: 88%
See 4 more Smart Citations
“…The pattern of data observed here is also consistent with findings from Bethell et al (2019) in which macaques showed behavioral inhibition (failure to respond at all to some stimuli) but not response slowing, which might cause one to call the procedure into question. However, it is possible that the lack of effect was due not to a failure of the procedure itself, but of the stimuli we selected.…”
Section: Experiments Onesupporting
confidence: 88%
“…This study provided a proof of concept indicating that response times can be used to indicate negative affect in apes. However, Bethell et al (2019) showed that macaques responded more slowly to pictures of objects than human intruders. This unexpected result, coupled with the fact that the response slowing procedure has not yet been shown to be effective with apes, suggests that the response slowing paradigm requires further validation for use with apes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations